"Is Life Worth Living?": The Role of Masculinity in the Way Men Aged Over 80 Talk About Living, Dying, and Suicide. Issue 5 (October 2020) - King, Kylie; Dow, Briony; Keogh, Louise; Feldman, Peter; Milner, Allison; Pierce, David; Chenhall, Richard; Schlichthorst, Marisa
Men aged 85 years and over have the highest rate of suicide of any age or gender group in Australia. However, little is known about their trajectory toward suicide. The objective of this study was to understand the role of masculine norms and other life factors in the suicidality of older men. Thirty-three men aged 80 years or more took part in a semistructured focus group or interview, and/or completed a survey. Participants were asked about the issues facing older men, well-being and aging, physical health challenges, social support, mental health and help-seeking, and suicide and suicide prevention. Five themes emerged: "finding out we're not invincible, " "active and tough, " "strong silent types, " "decision makers, " and "right to die." Participants spoke about masculine norms that had influenced their lives as providers and decision makers, and now influenced how they coped with aging and their journey toward death. For some participants, suicide was seen to be a rational alternative to dependence in their final years. Suicide prevention should adopt a gendered approach and be cognizant of the influence of gender roles and masculinity in older men's lives. Further research and prevention efforts should be mindful of the impact of masculine norms of self-reliance and control on an older man's decision to end his life. Suicide prevention efforts should work to reduce stigma around the challenges of aging, maximize opportunities for control, facilitate social connection, and improve residential aged care.